2015
DOI: 10.1021/es505590j
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Desorption of U(VI) on Functionalized Graphene Oxides: A Combined Experimental and Theoretical Study

Abstract: The adsorption and desorption of U(VI) on graphene oxides (GOs), carboxylated GOs (HOOC-GOs), and reduced GOs (rGOs) were investigated by batch experiments, EXAFS technique, and computational theoretical calculations. Isothermal adsorptions showed that the adsorption capacities of U(VI) were GOs > HOOC-GOs > rGOs, whereas the desorbed amounts of U(VI) were rGOs > GOs > HOOC-GOs by desorption kinetics. According to EXAFS analysis, inner-sphere surface complexation dominated the adsorption of U(VI) on GOs and HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
183
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 497 publications
(192 citation statements)
references
References 68 publications
7
183
0
2
Order By: Relevance
“…The bands at *518, *587, and *814 cm -1 suggest the complete crystalline structure of NKF-6 zeolite. The peak at *2462 cm -1 assigns to the vibration of adsorbed CO 2 species on NKF-6 zeolite surface, and the peaks at *3430 and *1633 cm -1 correspond to the bend vibration of zeolitic water in the NKF-6 zeolite [26,27,42]. The XRD pattern of NKF-6 zeolite ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The bands at *518, *587, and *814 cm -1 suggest the complete crystalline structure of NKF-6 zeolite. The peak at *2462 cm -1 assigns to the vibration of adsorbed CO 2 species on NKF-6 zeolite surface, and the peaks at *3430 and *1633 cm -1 correspond to the bend vibration of zeolitic water in the NKF-6 zeolite [26,27,42]. The XRD pattern of NKF-6 zeolite ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the adsorption (light off) of U(VI) by the ZnO/ rectorite catalyst without visible light irradiation was also checked and approximately 24.5 % of U(VI) was adsorbed in the dark after 180 min. This result shows that the ZnO/ rectorite catalyst had a high adsorption capacity for U(VI), which is in favor of the photoreduction of U(VI) [25,26]. The photoreduction activity of the ZnO/rectorite sample was all much higher than that of the ZnO, which indicated that the as-prepared samples may combine the adsorbility of rectorite and the catalytic ability of ZnO together to remove U(VI) from its aqueous solutions efficiently.…”
Section: Photoreduction Of U(vi)mentioning
confidence: 87%
“…For the presence of both surface complexes and surface (co)precipitates, it is very difficult to distinguish them on attapulgite surface. The surface (co)precipitates and inner-sphere surface complexes can be distinguished from the bond distances of Eu-O in the first coordination shell or the bond distances of Eu-O-Eu in the second coordination shell from the EXAFS analysis [47,48]. From the acid-base titration curve, the surface site concentration of attapulgite was calculated to be 2.425 9 10 -3 mol/g [20].…”
Section: Effect Of Ionic Strength and Phmentioning
confidence: 99%